2005
DOI: 10.1007/bf03018587
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged (more than ten hours) neuromuscular blockade after cardiac surgery: report of two cases

Abstract: P Pu ur rp po os se e: : We examine two cases of prolonged neuromuscular blockade (NMB) after cardiac surgery. To the best of our knowledge, these are the first reported cases of complete paralysis lasting more than ten hours after surgery.C Cl li in ni ic ca al l f fe ea at tu ur re es s: : We attribute the extended durations of NMB (more than ten hours) to high doses of NMB drugs in combination with magnesium sulphate and moderate renal failure. Advanced age, hepatic disease, aminoglycoside exposure, hypocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…Cases similar to our own are exceptional 4 . Only the case reported by Olivieri et al, 5 involving a10‐h duration of block was similar.…”
Section: Discussionsupporting
confidence: 82%
“…Cases similar to our own are exceptional 4 . Only the case reported by Olivieri et al, 5 involving a10‐h duration of block was similar.…”
Section: Discussionsupporting
confidence: 82%
“…25 Hypokalaemia and hypocalcaemia were shown to augment neuromuscular block, as a recent report laid emphases to the fact that hypokalaemia and hypocalcaemia could have significantly contributed to rocuronium prolonged paralysis that lasted for several hours after surgery. 26 In our study, patients manifested dilutional Table 3 Rocuronium time-course of action. Data are given as mean (SD) for n=14 in each group.…”
Section: Discussionmentioning
confidence: 54%
“…Prolonged neuromuscular blockade is rare, but not unique. Similar cases[24] have demonstrated that even a single intubating dose of an intermediate-acting neuromuscular blocking agent can cause prolonged neuromuscular blockade, which should mandate the need for neuromuscular assessment every time additional neuromuscular blocking agent is considered. Failure to objectively assess neuromuscular function may result in prolongation of a profound neuromuscular blockade, as was seen in our case.…”
Section: Discussionmentioning
confidence: 99%